Micropropagation of banana (Musa acuminata) through proliferation of axillary shoots - MANCHANDA, POOJA; KAUR, AJINDER; GOSAL, SATBIR SINGH (The Indian Journal of Agricultural Sciences, 2012)
An efficient and reproducible micropropagation protocol was developed for mass multiplication of the elite banana (Musa acuminata L.) cultivar Grand Naine through axillary shoot proliferation. In vitro multiplication of banana was studied. Conventional propagation through suckers has disadvantages like low multiplication rate (5 to 10 in number depending upon variety), lack of uniform plant size and transmission of pathogens from one generation to the next generation. Application of micropropagation technique for large scale production of elite clones is an effective and superior alternative to propagation through conventional cuttings of Musa spp. Shoot tips were cultured on MS medium supplemented with 5.0 mg/l BAP. Observations were recorded at the end of each subculture, after three weeks of shifting on a new medium. It was noted that suckers of same genotype exhibited different shoot multiplication rates under in vitro conditions. On an average, upto 175.57 shoots were produced from each shoot tip after seven subculturings.